Impact of Platelet-Rich Plasma on Arthroscopic Repair of Small- to Medium-Sized Rotator Cuff Tears: A Randomized Controlled Trial. Issue 9 (13th September 2016) - Holtby, Richard; Christakis, Monique; Maman, Eran; MacDermid, Joy C.; Dwyer, Tim; Athwal, George S.; Faber, Kenneth; Theodoropoulos, John; Woodhouse, Linda J.; Razmjou, Helen
Background: Increased interest in using platelet-rich plasma (PRP) as an augment to rotator cuff repair warrants further investigation, particularly in smaller rotator cuff tears. Purpose: To examine the effectiveness of PRP application in improving perioperative pain and function and promoting healing at 6 months after arthroscopic repair of small- or medium-sized rotator cuff tears. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: This was a double-blinded randomized controlled trial of patients undergoing arthroscopic repair of partial- or full-thickness rotator cuff tears of up to 3 cm who were observed for 6 months. Patients were randomized to either repair and PRP application (study group) or repair only (control group) groups. The patient-oriented outcome measures utilized were the visual analog scale (VAS), the Short Western Ontario Rotator Cuff Index (ShortWORC), the American Shoulder and Elbow Surgeons (ASES) form, and the Constant-Murley Score (CMS). Range of motion (ROM) and inflammatory and coagulation markers were measured before and after surgery. Magnetic resonance imaging was used at 6 months to assess retear and fatty infiltration rate. Results: Eighty-two patients (41 males) with a mean age of 59 ± 8 years were enrolled; 41 patients were included in each group. Both the PRP and control groups showed a significant improvement in their pain level based on the VAS within the first 30 days ( P < .0001), with the PRP group reporting less pain than the control group ( P = .012), which was clinically significantly different from days 8 through 11. The PRP group reported taking less painkillers ( P = .026) than the control group within the first 30 days. All outcome measure scores and ROM improved significantly after surgery ( P < .0001), with no between-group differences. No differences were observed between groups in inflammatory or coagulation marker test results ( P > .05), retear (14% vs 18% full retear; P = .44), or fatty infiltration rate ( P = .08). Conclusion: The PRP biological augmentation for repair of small- to medium-sized rotator cuff tears has a short-term effect on perioperative pain without any significant impact on patient-oriented outcome measures or structural integrity of the repair compared with control group.